Manajemen Produksi Pemberitaan Isu Kekerasan Seksual dan Potensi Represi - Ningrum, Kisna Hesti; Arifina, Anisa Setya; Pembayun, Jaduk Gilang (Jurnal Studi Jurnalistik, 2023)
The issue of sexual violence is one of the issues that is often attacked by the media. Konde.co is an alternative media with the perspective of women and minorities who have experienced repression in the form of digital attacks and verbal violence when reporting sexual violence. This study aims to explain how Konde.co's editorial management in reporting the issue of sexual violence in the midst of potential repression. This study uses a qualitative method with a case study approach. Data collection techniques used are interviews, observation, and documentation studies. Based on the results of the research, it is known that Konde.co carries out editorial management, such as planning, organizing, actuating, and controlling in reporting on issues of sexual violence with a gender perspective, where reporting is always on the side of the victim. The findings of further research, Konde.co anticipate repression in reporting sexual violence by implementing a Journalistic Code of Ethics and guidelines for reporting sexual violence, prioritizing the protection of journalists' safety in covering sexual violence, and mitigating digital attacks.